Accounting of value of ecosystem services in the desert: an example of the Kubuqi Desert ecosystem - Liu, Yanbing; Kong, Lingqiao; Jiang, Chaoqiang; Zhang, Xiaoling; Ouyang, Zhiyun (Frontiers in Earth Science, 2024)
Ecological products and ecosystem services are essential for human survival and development. Gross Ecosystem Product (GEP) is a method to combine the value of ecosystem services and can reflect the status of ecosystem and ecological conservation and restoration performance. The conservation and restoration of desert ecosystems play an important role in the global cultivated land expanding, food security ensuring and human well-being improving. However, ecosystem services and value of GEP in desert have been neglected. Taking Kubuqi Desert ecosystem as an example, this study evaluated the pattens, GEP value and its change of Kubuqi Desert ecosystem from 2000 to 2020. Our study found that 1) over the past 20 years, the areas of wetlands, forests, grasslands, and shrubs in Kubuqi desert ecosystem had increased by 100.65%, 6.05%, 2.24% and 2.03%, respectively, while that of desert had decreased by 10.62%; 2) the GEP of Kubuqi in 2020 was 55.48 billion CNY, among which its sandstorm prevention value was the highest (39.39%); 3) The value of ecosystem services in Kubuqi desert ecosystem were all increased over the 20-year period and the largest increase came from sandstorm prevention (increased by 195.09%). This study emphasis how GEP accounting can promote the desert conservation and restoration, quantifies the contribution of desert ecosystems to human well-being, and provide future GEP accounting suggestion for desert ecosystem. This study can provide scientific information of the conservation and restoration for global desert ecosystems.